1999
DOI: 10.1021/je990134w
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of 2-Hydroxybenzoic Acid in Select Organic Solvents at 298.15 K

Abstract: Experimental solubilities are reported for 2-hydroxybenzoic acid dissolved in 1-propanol, 2-propanol, 1-butanol, 2-butanol, 2-methyl-1-propanol, 2-methyl-2-propanol, 1-pentanol, 1-octanol, dibutyl ether, 1,4-dioxane, tetrahydrofuran, ethyl acetate, butyl acetate, 2-propanone, 2-butanone, and cyclohexanone at 298.15 K. Results of these measurements reveal that the observed solubilities in the eight alcohol solvents fall within a fairly narrow mole fraction range of each other. 2-Hydroxybenzoic acid is more solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
(17 reference statements)
2
14
0
Order By: Relevance
“…Table 2 lists the densities of the saturated solutions, experimental and correlated, solubility values of salicylic acid in water, 1-propanol, 2-propanol, and 2-propanone solutions at different temperatures. As expected, the solubility of salicylic 1 and 0.1817 1 respectively for 1-propanol, 2-propanol, and 2-propanone with the results of this work 0.132, 0.144, and 0.137 respectively for 1-propanol, 2-propanol, and 2-propanone reveal that there is almost agreement between them. As it is reported and discussed by Matsuda et al, there are considerable differences between reported solubility values for salicylic acid from different groups.…”
Section: ■ Introductionsupporting
confidence: 89%
“…Table 2 lists the densities of the saturated solutions, experimental and correlated, solubility values of salicylic acid in water, 1-propanol, 2-propanol, and 2-propanone solutions at different temperatures. As expected, the solubility of salicylic 1 and 0.1817 1 respectively for 1-propanol, 2-propanol, and 2-propanone with the results of this work 0.132, 0.144, and 0.137 respectively for 1-propanol, 2-propanol, and 2-propanone reveal that there is almost agreement between them. As it is reported and discussed by Matsuda et al, there are considerable differences between reported solubility values for salicylic acid from different groups.…”
Section: ■ Introductionsupporting
confidence: 89%
“…The concentration of each diluted solution was calculated from a BeerLambert law absorbance versus concentration curve generated from the measured absorbances of nine carefully prepared standard solutions of known solute concentration. The analysis wavelengths and concentration ranges used for each solute have been reported in our earlier publications [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. Molar concentrations were converted into mole fraction solubilities using the mass of the sample analyzed, molar masse of 2-butoxyethanol and the respective solutes, volume of the volumetric flasks, and any dilutions needed to get the measured absorbances on the Beer-Lambert law curve.…”
Section: Solubility Measurementsmentioning
confidence: 99%
“…Molar concentrations of the diluted solutions were determined from a Beer-Lambert law absorbance versus concentration working curve for nine standard solutions of known concentration. The analysis wavelengths and concentration ranges used for each solute have been reported in earlier solubility publications [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Solubility Measurementsmentioning
confidence: 99%